THE PHARMACISTS' AND MOBILE APPLICATIONS' ROLE IN THE TREATMENT OF HYPERTENSION. (June 2022) - Tarnovski, Lorka; Frkanec, Stjepan; Frkanec, Stjepan; Katic, Luka; Strbac, Tea; Lovakovic, Josip; Susnjara, Petar; Rasic, Fran; Sekulic, Mislav; Josipovic, Josipa; Begic, Zvonimir; Barisic, Klara; et al.
Abstract : Objective: Poor adherence is the main reason for inadequate blood pressure control. Pharmacists are highly accessible healthcare professionals, and it has been reported that community pharmacist-led interventions improved patients' BP control and outcomes. Some authors reported on the beneficial effects of mobile applications on better drug adherence. The aim of this study was to identify subjects in the general population who may benefit from such interventions. Design and method: A total of 1228 subjects enrolled in the EHUH 2 study (a random sample, nationwide survey) and 424 participants of the Hunt on the Silent Killer (HSK) (opportunistic screening on islands) were included in this analyses. The same questionnaire was applied containing questions about health issues, therapy, habits, and opinion on pharmacists' and mobile applications' (MA) role in hypertension treatment. Results: The binomial logistic regression analysis showed a significant model when comparing positive and negative answers for the following: the participants were more likely to be in favour of pharmacists' role if they had a positive history of angina pectoris ( = 1.333, p = 0.016), diabetes mellitus ( = 1.125, p < 0.001), dyslipidemia ( = 1.326, p < 0.001), or being treated for hypertension ( = 1.326, p < 0.001) in the HSK, and in the EHUH 2 study if they suffered a stroke (100%). Socio-demographic factors had no impact on the pharmacists' role in the general population. However, at islands significantly enhanced negative responses in case of lower household income (35%), married state (29%) and employed subjects (17%) were observed. The participants were more likely to be in favour of MA if they had a positive history of hypertension, have higher income and were married. Interestingly, the history of cardiovascular diseases indicated more negative responses. Conclusions: The participants were generally in favour of MA, which may confirm the need to digitalise the healthcare system, but it was more enhanced in participants with a higher socio-demographic status. Pharmacists-led interventions (lifestyle support and adherence increasing programs) have to be individualized.